High Li+ and Na+ Conductivity in New Hybrid Solid Electrolytes based on the Porous MIL‐121 Metal Organic Framework. Issue 16 (25th February 2021) - Zettl, Roman; Lunghammer, Sarah; Gadermaier, Bernhard; Boulaoued, Athmane; Johansson, Patrik; Wilkening, H. Martin R.; Hanzu, Ilie
Abstract: Solid‐state electrolytes (SSEs) can leapfrog the development of all‐solid‐state batteries (ASSBs), enabling them to power electric vehicles and to store renewable energy from intermittent sources. Here, a new hybrid Li + and Na + conducting SSE based on the MIL‐121 metal‐organic framework (MOF) structure is reported. Following synthesis and activation of the MOF, the free carboxylic units along the 1D pores are functionalized with Li + or Na + ions by ion exchange. Ion dynamics are investigated by broadband impedance spectroscopy and by 7 Li and 23 Na NMR spin‐lattice relaxation. A crossover at 50 °C (Li + ) and at 10 °C (Na + ) from correlated to almost uncorrelated motion at higher temperature is observed, which is in line with Ngai's coupling model. Alternatively, in accordance to the jump relaxation model of Funke, at low temperature only a fraction of the jump processes are successful as lattice rearrangement in the direct vicinity of Li + (Na + ) is slow. 1 H NMR unambiguously shows that Li + is the main charge carrier. Conductivities reach 0.1 mS cm −1 (298 K, Na + ) while the activation energies are 0.28 eV (Li + ) and 0.36 eV (Na + ). The findings pave the way towards development of easily tunable and rationally adjustable high‐performance MOF‐based hybrid SSEs for ASSBs. Abstract : The MIL‐121 metal–organic framework (MOF) is ion‐exchanged allowing fast Li + and Na + transport along the inner channels of the framework. For a hybrid solid electrolyte based on a MOF structure, a conductivity of 0.1 mS cm −1 for Na + (30 °C) is an amazing value opening new perspectives on ion‐conducting MOFs.